PENGARUH PROFITABILITAS, LIKUIDITAS, SOLVABILITAS DAN UKURAN PERUSAHAAN TERHADAP KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN PADA PERUSAHAAN MANUFAKTUR DI BEI - Jessica Carolina; Vargo Christian L. Tobing (LPPM Universitas Putera Batam, 2019)
The timeliness of submitting financial statements is a rule that must be applied by all companies. Based on the Decree of the Chairperson of the Capital Market and Financial Institution Supervisors with number: KEP-431/BL/2012 stating that public companies that have effective registration must submit annual reports to BAPEPAM and LK no later than four months after the end of the financial year. This study aims to examine the effect of profitability, liquidity, solvency and firm size on the timeliness of financial statement submission. The population in this study is a consumer goods manufacturing sector manufacturing company listed on the Indonesia Stock Exchange. The sample was selected as many as 21 companies using the purposive sampling method. The analytical method is logistic regression. The data used is secondary data obtained through the web.idx.id website in the form of annual financial statements for the periode 2013-2017. The results of the study were tested using the SPSS version 24 application which showed that partial profitability (ROA), liquidity (CR), solvency (DAR) dan company siz